If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy = 3x + -9 Reorder the terms: xy = -9 + 3x Solving xy = -9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -3x + xy = -9 + 3x + -3x Combine like terms: 3x + -3x = 0 -3x + xy = -9 + 0 -3x + xy = -9 Reorder the terms: 9 + -3x + xy = -9 + 9 Combine like terms: -9 + 9 = 0 9 + -3x + xy = 0 The solution to this equation could not be determined.
| x+127+x+x+7=180 | | h+9=21 | | 8x=23+7y | | x+38=x+13 | | -6(4x+3)=6 | | 6+6x=3(2x+3) | | -5x+9y=-12 | | 9+6t-5=4t+40-2t | | 7+r=13 | | 7+q=12 | | 2x(1+6)8(4-2)=x | | 6y+9=10y+9 | | 4.2*x-9=3(1.2x+4) | | 2+s=9 | | 5c=15 | | 126=x+.30 | | 15-b=6 | | 5-q=4 | | 395=495-x | | 8v^2-3v-61=0 | | 3x^2-15x-50=0 | | 4-x^2=0 | | 15-m=6 | | x-2y=15 | | 14-a=6 | | 6-7x+11=-2(-4x+1) | | 3-j=2 | | 5x^2+18x+19=0 | | x-6(.17x+2)=-12 | | 10-s=6 | | r*(p*q)=(r*p)*q | | 6x+13=47 |